2018
DOI: 10.1038/s41598-018-19686-3
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Functional Structure of Wintering Waterbird Communities Associated with Ecological Differences

Abstract: Ecological differences may be related to community component divisions between Oriental (west) and Sino-Japanese (east) realms, and such differences may result in weak geographical breaks in migratory species that are highly mobile. Here, we conducted comparative phylogenetic and functional structure analyses of wintering waterbird communities in southern China across two realms and subsequently examined possible climate drivers of the observed patterns. An analysis based on such highly migratory species is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Environmental filtering would result in negative SESFRic and SESFDis values by allowing only a set of species with certain functional traits to persist and by forcing most of the biomass into a small trait space (Liu, Swenson, Zhang, & Ma, 2013;Mason et al, 2005). These findings were also in concordance with some of the previous studies on waterbirds that reported functionally clustered waterbirds communities (the western populations in Che et al, 2018;summer season in Che et al, 2019;Li et al, 2019).…”
Section: Functional Diversitysupporting
confidence: 88%
See 1 more Smart Citation
“…Environmental filtering would result in negative SESFRic and SESFDis values by allowing only a set of species with certain functional traits to persist and by forcing most of the biomass into a small trait space (Liu, Swenson, Zhang, & Ma, 2013;Mason et al, 2005). These findings were also in concordance with some of the previous studies on waterbirds that reported functionally clustered waterbirds communities (the western populations in Che et al, 2018;summer season in Che et al, 2019;Li et al, 2019).…”
Section: Functional Diversitysupporting
confidence: 88%
“…We simulated null distributions of FD measures for the observed species richness values and abundances to see if the observed FD values differ from those of randomly assembled communities. For a community with n species, the null model was created by sampling n species randomly from the regional pool-defined as cumulative list of wintering waterbird species from the corresponding lake-without replacement 999 times and calculating FD indices for these 999 random communities (Che et al, 2018;Seymour et al, 2015;Swenson, 2014). In this way, species richness and community size are kept the same for each community, while only the names of the species are shuffled (Che et al, 2018;Swenson, 2014 (Mouchet, Villéger, Mason, & Mouillot, 2010).…”
Section: Null Modelsmentioning
confidence: 99%
“…In contrast to functional NRI capturing the overall dissimilarity of the taxa, functional NTI is more sensitive to the distribution of lineages close to the tips of trees (Swenson, ). Therefore, NRI might be more influenced by factors that operated in the distant past, while NTI patterns are likely to reflect more recent changes (Che et al, ). This pattern provides further evidence for the importance of environmental filtering over a variety of temporal scales in assembly processes of assemblages comprised of mobile species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to functional NRI capturing the overall dissimilarity of the taxa, functional NTI is more sensitive to the distribution of lineages close to the tips of trees (Swenson, 2014 (Li et al, 2019), providing limited opportunities for resource partitioning. Similar to heterogeneous habitats, wetlands with better landscape connectivity can attract more waterbird species (Che et al, 2018), resulting in functional overdispersion, particularly in winter. However, waterbirds may rely more on local environment during the breeding season when communities were functionally clustered (Wiens, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various studies comparing the functional and phylogenetic structure of animal assemblages (Devictor et al, 2010;Machac et al, 2011;Dehling et al, 2014;Sobral and Cianciaruso, 2016;Che et al, 2018), as well as plant assemblages (Kraft and Ackerly, 2010;Cianciaruso et al, 2012), there are few reports on the trend and relationship between the functional and phylogenetic structure of different traits along the elevational gradient. Actually, elevational gradients can suitably reflect competition and environmental filtering.…”
Section: Introductionmentioning
confidence: 99%